Matoa Brand Watch Products Online Purchase Decision on Makassar City Students - Mujahid; Yasir Haskas; Nasyirah Nurdin; Dicky Adhitirta (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The purchase decision is a problem identification process carried out with several series of processes in accordance with consumer wants and needs. This study aims to analyze how the decision to purchase Matoa watch products. In this study, the method used is a qualitative method with data collection techniques using the Research library technique and field studies or field research by interviewing 5 informants. Based on the research results, the results of the decision making of Matoa watches through online media are based on several factors such as problem recognition, information search, information before using the product, purchase decisions, and post-purchase evaluation.